New Silver Complexes with Mixed Thiazolidine and Phosphine Ligands as Highly Potent Antimalarial and Anticancer Agents - Nur Rahimah Fitrah Mohd Sofyan; Fariza Juliana Nordin; Mohd Ridzuan Mohd Abd Razak; Syahrina Nur ‘Ain Abdul Halim; Nur Adila Fatin Mohd Khir; Amirrudin Muhammad; Nor Fadilah Rajab; Rozie Sarip (Journal of Chemistry)
Five silver(I) complexes containing a mixed ligand system of phosphine and thiazolidine were successfully synthesized. The structural information of the complexes was assembled using various spectroscopic techniques such as CHN elemental analysis, Fourier transformed infrared (FTIR), 1H, 13C, and 31P{1H} NMR spectroscopy, and thermogravimetric analysis (TGA). A bidentate phosphine ligand acted as a chelating agent which bond to the silver in 1 : 2 molar ratios. Meanwhile, thiazolidine was attached to the silver in a 1 : 1 molar ratio. The antiplasmodial properties of all synthesized complexes were investigated on chloroquine-resistant P. falciparum parasite via HRP2 assays and cytotoxicity tests on Vero cells. Of all the synthesized complexes, complex 2 showed the highest SI value (more than 12.4) followed by complex 5 (6.6). The potent properties of compounds 2 and 5 were also noted in the in vitro antiproliferative assays involving MDA-MB-231 and MCF-7 breast cancer cell lines as well as HT-29 colon cancer cell line. Complex 2 was selective for MDA-MB-231 cells (GI50 = 1.9 ± 0.3 µM), while complex 5 acted predominantly on breast carcinoma cells (GI50 MDA-MB-231 = 4.7 ± 1.1 µM; MCF-7 = 2.9 ± 0.9 µM) instead of colon carcinoma (HT-29) cells (GI50 = 15.1 ± 1.9 µM).